Cloning, Expression, and Purification of a Nitric Oxide Synthase-Like Protein from Bacillus cereus. (30th November 2009) - Montgomery, Heather J.; Dupont, Andrea L.; Leivo, Hilary E.; Guillemette, J. Guy
Abstract : The nitric oxide synthase-like protein from Bacillus cereus (bcNOS) has been cloned, expressed, and characterized. This small hemeprotein (356 amino acids in length) has a mass of 43 kDa and forms a dimer. The recombinant protein showed similar spectral shifts to the mammalian NOS proteins and could bind the substrates L-arginine andN G -hydroxy-L-arginine as well as the ligand imidazole. Low levels of activity were recorded for the hydrogen peroxide-dependent oxidation ofN G -hydroxy-L-arginine and L-arginine by bcNOS, while a reconstituted system with the rat neuronal NOS reductase domain showed no activity. The recombinant bcNOS protein adds to the complement of bacterial NOS-like proteins that are used for the investigation of the mechanism and function of NO in microorganisms.